The Influence of Staff Knowledge Level on Health Information System Use at Community Health Centers in Malang City - Soultoni Akbar, Prima; Maulidah Hariez, Tsalits (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
One important ICT implementation in the healthcare sector is the Health Information System (HIS). There is limited research specifically examining the knowledge of community health center staff regarding readiness to use a HIS. This study aims to determine the level of staff knowledge regarding HIS use. The researchers used this approach to determine the influence of community health center staff knowledge (the independent variable) on readiness to use a health information system. The sample size in this study was 41 respondents. The sampling technique used in this study was random sampling (probability sampling). There was an effect of knowledge level on readiness to use a health information system (t = 17.96, p = <0.001). The level of knowledge of community health center staff regarding readiness to use a health information system was quite good.